Properties of concrete incorporating locally produced Portland limestone cement - Fatma Shaker; Ahmed Rashad; Mohamed Allam (Ain Shams Engineering Journal, 2018)
Blended cements are increasingly being used in concrete to reduce the amount of clinker in the cement, thus achieving both economic and environmental gains. The use of limestone as a component of Portland cement is now common practice worldwide. Reducing the amount of cement clinker with limestone additions is considered a highly efficient way of saving natural resources, saving energy and lowering the carbon dioxide emissions. The main objective of this research is to investigate the effect of using locally produced Portland limestone cement (PLC) on the concrete characteristics. Tests determining the fresh, hardened and durability properties of concrete were conducted on PLC concrete specimens and then compared to similar results of concrete made with Ordinary Portland cement. This investigation concluded that concrete made with CEM II (A-L) accomplished competitive results with OPC CEM I 42.5 concrete. Furthermore, all PLC concretes achieved lower water permeability compared to OPC concretes. Keywords: Ordinary Portland cement (OPC), Portland limestone cement (PLC), Portland composite cement, Water permeability, Sulfate resistance, Rapid chloride penetration